2022
DOI: 10.3390/life12101665
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Chemistry Experiments Using Microfluidic Devices

Abstract: Microfluidic devices are small tools mostly consisting of one or more channels, with dimensions between one and hundreds of microns, where small volumes of fluids are manipulated. They have extensive use in the biomedical and chemical fields; however, in prebiotic chemistry, they only have been employed recently. In prebiotic chemistry, just three types of microfluidic devices have been used: the first ones are Y-form devices with laminar co-flow, used to study the precipitation of minerals in hydrothermal ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Inorganic precipitation reactions can form a wealth of spatial structures ranging from complex three-dimensional microstructures to macroscopic membranes that compartmentalize the reaction system and self-regulate the formation of additional precipitate. Many of these structures share no similarities with euhedral crystals but are smoothly curved and reminiscent of shapes more closely associated with living systems. This morphological similarity between abiotic and biological systems continues to cause problems for the identification of Earth’s earliest microfossils as well as the search for remnants of life on other planets. Inorganic precipitate membranes are also of interest to origins of life research. In this context, hydrothermal vents have attracted considerable attention. They arise near fissures on the ocean floor, eject mineral-rich hot water into the cold ocean, and erect tall chimney structures. These precipitate towers are usually classified as white or black smokers depending on their hue and mineral composition. , Black smokers are rich in iron and nickel precipitates, whichas slurries in laboratory settingscatalyze the carbon-monoxide-driven formation of α-hydroxy and α-amino acids. , …”
Section: Introductionmentioning
confidence: 99%
“…Inorganic precipitation reactions can form a wealth of spatial structures ranging from complex three-dimensional microstructures to macroscopic membranes that compartmentalize the reaction system and self-regulate the formation of additional precipitate. Many of these structures share no similarities with euhedral crystals but are smoothly curved and reminiscent of shapes more closely associated with living systems. This morphological similarity between abiotic and biological systems continues to cause problems for the identification of Earth’s earliest microfossils as well as the search for remnants of life on other planets. Inorganic precipitate membranes are also of interest to origins of life research. In this context, hydrothermal vents have attracted considerable attention. They arise near fissures on the ocean floor, eject mineral-rich hot water into the cold ocean, and erect tall chimney structures. These precipitate towers are usually classified as white or black smokers depending on their hue and mineral composition. , Black smokers are rich in iron and nickel precipitates, whichas slurries in laboratory settingscatalyze the carbon-monoxide-driven formation of α-hydroxy and α-amino acids. , …”
Section: Introductionmentioning
confidence: 99%
“…It is now well-known that there are multifold advantages of using microfluidic devices over macroscopic ones owing to their portability, ease of use, availability of a higher surface-to-volume ratio for the process intensified engineering processes, control over the reagent parameters owing to their usage of smaller volumes, and capacity to bring in the aspects of very-large-scale integration (VLSI) for a larger throughput and multitasking, among others. Thus, such microfluidic platforms are found to appear in diverse modern-day functionalities that include drug delivery, point-of-care diagnostics, tissue engineering, high-throughput screening, protein crystallization, and deoxyribonucleic acid (DNA) analysis. , In particular, the success in the integration of multiplexing of microfluidic devices on the lab-on-a-chip , platforms has led to the development of portable laboratory prototypes in the diverse areas of biology, chemistry, medicine, , and engineering. , However, several limitations related to microfluidic platforms have emerged over the years, including the diffusion-limited mixing capacity, a relatively lower throughput, and crowding–clogging of transport materials, among others. Of late, such areas have become intense scientific and engineering research.…”
Section: Introductionmentioning
confidence: 99%
“…Research on multi-metal and other more complex precipitates has only recently begun. , For example, Wang et al studied precipitate membranes formed from seawater and showed the highly selective precipitation of Mg­(OH) 2 compared to CaCO 3 . Such work is important because the porous walls of vent chimneys are composed of a wide variety of minerals containing Fe, S, Mg, Ca, and Ba as well as trace metals, such as Ni, Co, Mn, Cu, and Zn. Moreover, the steep cross-membrane gradients and overall non-equilibrium conditions in hydrothermal vents are at least partially captured by microfluidic experiments and allow us to study how these conditions affect the average product composition and possible compositional gradients. , …”
Section: Introductionmentioning
confidence: 99%